846. TRICYRTIS MACRANTHA: Liliaceae. (September 2016) - Ikeda, Hiroshi
Summary: Tricyrtis macrantha Maxim. (Liliaceae), an endemic species to Japan, is illustrated. It is distributed in a small area in Shikoku (Kochi Prefecture), and grows on limestone cliffs. Tricyrtis macrantha and its allied species, T. macranthopsis Masam., distributed in Kii Peninsula in western Honshu, and T. ishiiana (Kitag. & T. Koyama) Ohwi & Okuyama, distributed in Pacific coast side of central Honshu, comprise one natural group.